Pelatihan dan Pendampingan Pembuatan Virgin Coconut Oil sebagai Alternatif Produk Unggulan dalam Upaya Meningkatkan Ekonomi Masyrakat Desa Manawa Gorontalo - Usman Usman; Victorson Taruh (Universitas Negeri Gorontalo, 2024)
There has been an increase in the price of cooking oil made from palm oil in Indonesia leading to shortages. Various efforts have been made to process alternative vegetable oils as a substitute for palm oil, one of which is pure coconut oil. Pure kalapa oil or VCO as a substitute for palm oil has great potential to be developed in Pohuawato village. Implementation of community service activities in Manawa Village, Patilaggio District, Pohuwato Regency with the background of community livelihoods in the agricultural and plantation sectors, especially with plantation products in the form of coconut, but community income is still low due to a lack of innovation in processing plantation products. Coconuts are sold raw to collectors without processing them first so the selling price is low. Therefore, assistance and training is needed for the community in Manawa Village, Patilaggio District, Pohuwato Regency to process plantation products. For this reason, this community service activity will provide outreach and training on making pure coconut oil (VCO) to the people of Tabongo Village. There are several programs that will be implemented regarding the problems that have been described, namely providing socialization on the use of coconuts to make pure coconuts (VCO), providing training on processing coconuts into innovative products and assistance with pure coconut oil businesses. With the training and assistance, it is hoped that the community in Manawa Village, Patilaggio District, Pohuwato Regency can provide solutions for processing coconut into products with high selling value that can increase family income.Terjadinya peningkatan harga minyak goreng berbahan baku kelapa sawit di Indonesia mengangkibatkan terjadinya kelangkaan. Berbagai usaha dilakukan untuk mengolah minyak nabati alternative sebagai pengganti minyak kelapa sawit, salah satunya adalah minyak kelapa murni. minyak kalapa murni atau vco sebagai pengganti minyak sawit sangat potensial untuk dikembangkan didesa pohuawato. Pelaksanaan kegiatan pengabdian masyarakat di Desa manawa Kecamatan Patilanggio Kabupaten Pohuwatodengan latar belakang mata pencaharian masyarakat di sektor pertanian dan perkebunan terutama dengan hasil perkebunan berupa Kelapa, namun penghasilan masyarakat masih rendah dikarenakan kurangnya inovasi dalam pengolahan hasil perkebunan. Kelapa dijual secara mentah kepada pengepul tanpa diolah terlebih dahulu sehingga harga jualnya rendah. Oleh karena itu diperlukan sebuah pendampingan dan pelatihan kepada masyarakat di Desa manawa Kecamatan Patilanggio Kabupaten Pohuwatountuk mengolah hasil perkebunan. Untuk itu pada kegiatan pengabdian masyarakat ini akan diberikan sosialisasi dan pelatihan pembuatan minyak kelapa murni (VCO) kepada masyarakat Desa Tabongo. Terdapat beberapa program yang akan dilaksanakan mengenai masalah yang telah diuraikan yakni akan memberikan sosialisasi pemanfaatan buah kelapa menjadi kelapa murni (VCO), memberikan pelatihan pengolahan kelapa menjadi produk yang inovatif dan pendampingan usaha minyak kelapa murni. Dengan adanya pelatihan dan pendampingan diharapkan masayarakat yang ada di Desa manawa Kecamatan Patilanggio Kabupaten Pohuwato dapat memberikan solusi pengolahan kelapa menjadi produk yang bernilai jual tinggi yang dapat meningkatkan penghasilan keluarga.